Persepsi Petani Terhadap Digitalisasi Pertanian untuk Mendukung Kemandirian Petani - Johan, Daniel; Maarif, M. Syamsul; Zulbainarni, Nimmi (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The importance of the role of farmers in the agribusiness system is not directly proportional to the welfare of the farmers themselves, this is because the bargaining power of farmers in the system is very low. If we look at the high capacity of rice production in Sambas Regency, it is hoped that it can be maximized by the implementation of agricultural digitization in this district, as well as being an example for the application of agricultural digitization in other districts. This study aims to to identify existing conditions that occur in agriculture in the Sambas Regency area, then analyze farmers' perceptions of agricultural digitization, and formulate a model for developing agricultural digitization to support farmers' self-reliance in Sambas. The scope of this research is only farmers in Sambas Regency, West Kalimantan as a contributor to 20% of food production, especially rice in West Kalimantan Province. This research includes causality research (cause and effect). The method used in this study is the Structural Equation Modeling (SEM) method and the analysis of the development of agricultural digitization models through the synthesis of SEM analysis and Focus Group Discussion (FGD) in order to advance the analysis. The results of the study describe farmers' perceptions, farmer characteristics, and the role of assistants farming has a significant influence on agricultural digitization, but for farmers' perceptions the effect is negative. Keywords: agricultural digitalization, assistants farming, farmer characteristics, farmers perception, FGD, SEM